2018
DOI: 10.1128/mcb.00302-17
|View full text |Cite
|
Sign up to set email alerts
|

A High-Resolution Genome-Wide CRISPR/Cas9 Viability Screen Reveals Structural Features and Contextual Diversity of the Human Cell-Essential Proteome

Abstract: To interrogate genes essential for cell growth, proliferation and survival in human cells, we carried out a genome-wide clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9 screen in a B-cell lymphoma line using a custom extended-knockout (EKO) library of 278,754 single-guide RNAs (sgRNAs) that targeted 19,084 RefSeq genes, 20,852 alternatively spliced exons, and 3,872 hypothetical genes. A new statistical analysis tool called robust analytics and normalization for knockout screens (RANKS) id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 79 publications
8
90
0
Order By: Relevance
“…When mammalian cells were screened for genes "required for proliferation and survival", Wang et al reported that the PolR1E (PAF53) gene was essential. This result was confirmed by Bertomeu et al (16) and others (50). Thus, we sought to determine the specific effect of knocking down PAF53 using the AID as both physiological and biochemical results should be apparent very rapidly.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…When mammalian cells were screened for genes "required for proliferation and survival", Wang et al reported that the PolR1E (PAF53) gene was essential. This result was confirmed by Bertomeu et al (16) and others (50). Thus, we sought to determine the specific effect of knocking down PAF53 using the AID as both physiological and biochemical results should be apparent very rapidly.…”
Section: Resultssupporting
confidence: 83%
“…They also reported they were essential for promoter-specific transcription (32,33 (34,35,49). Most recently, several CRISPR/Cas9 based screenings of the mammalian genome identified PAF53 and PAF49 as being "essential" genes (16,17), which was confirmed when we found that we could not isolate cell lines that failed to express PAF53 (50).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…In order to identify Mubritinib’s target pathway, we then carried out a whole-genome CRISPR/Cas9 screen in the presence or absence of Mubritinib treatment (Fig. S4a and Read files 1-3), as previously described 44 . For this purpose, we used the B cell precursor leukemia cell line NALM-6, which, similar to poor outcome AML patient cells, is sensitive to Mubritinib (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have observed that cancer cell lines exhibit highly variable genetic dependencies for cellular fitness (Bertomeu et al, 2018; Blomen et al, 2015; Hart et al, 2015; Hart et al, 2017a; McDonald et al, 2017; Meyers et al, 2017; Tsherniak et al, 2017; Wang et al, 2015; Wang et al, 2017b) in a manner that reflects the diverse genomic and transcriptomic alterations a cell may accumulate during tumorigenesis. Project Achilles (Broad Institute of MIT and Harvard) seeks to systematically map genetic vulnerabilities across large collections of cancer cell lines, including the Cancer Cell Line Encyclopedia (CCLE) (Barretina et al, 2012), and has recently performed genome-scale perturbation screens in 501 cancer cell lines using RNA interference (RNAi) (Tsherniak et al, 2017) and in 342 cancer cell lines using CRISPR-Cas9 (Meyers et al, 2017).…”
Section: Introductionmentioning
confidence: 99%